THE IMPACT OF CASH FLOW ON STOCK RETURNS: A CASE STUDY OF TEXTILE AND GARMENT COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Hayatul Putri, Cut Misra; Ristati, Ristati; Bahri, Halida; Maulina, Isra; Syamni, Ghazali (J-ISCAN: Journal of Islamic Accounting Research, 2024)
In the modern economy, the capital market is a source of external financing for companies. The capital market offers companies the opportunity to compete fairly to attract investors who invest in their companies with expectations of high returns. One of the company performance parameters that attracts the attention of investors and creditors is the cash flow statement.This study aims to determine the impact of operating cash flow, investment cash flow, and financing cash flow on the stock earnings of textile and garment companies on the Indonesian Stock Exchange. The method used to analyze the relationship between independent and dependent variables is panel data regression analysis. As a result, operating cash flow has a positive and significant impact on the stock returns of Textile and Garment companies on the Indonesia Stock Exchange, while investment cash flow has a negative and significant impact on the stock returns of Textile and Garment companies on the Indonesia Stock Exchange. was given, funding cash flow significantly positively impacted equity returns. Contributed to the return of shares in a textile and garment company on the Indonesian Stock Exchange.